2017
DOI: 10.1016/j.jpsychires.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Temporal associations between affective instability and dysregulated eating behavior in bulimia nervosa

Abstract: Prior research suggests that the construct of emotional instability may be salient to bulimia nervosa (BN), but no study to date has used ecological momentary assessment (EMA) to examine its temporal association with binge eating and purging. In the current study, 133 women with DSM-IV BN used portable digital devices to provide multiple daily negative affect (NA) and positive affect (PA) ratings and record eating disorder behaviors over 2 weeks. Two state-of-the art indices quantified affective instability: p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 41 publications
4
27
0
Order By: Relevance
“…This is in line with other research that found that urgency, especially negative urgency, was associated with bingeing and purging behaviours, as well as subjective loss of control of food intake (Claes et al ., , Claes et al ., ; Fischer et al ., ; Racine et al ., ; Wolz et al ., ). Being that neuroimaging evidence has suggested that negative affect increases the rewarding value of food (Bohon & Stice, ) and that emotion dysregulation is associated with excess weight (Steward et al ., ), our results lend support to the notion that bingeing behaviours could mainly be negatively reinforcing (Berner et al ., ). Other researchers have found the tendency to act rashly when experiencing strong emotions (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…This is in line with other research that found that urgency, especially negative urgency, was associated with bingeing and purging behaviours, as well as subjective loss of control of food intake (Claes et al ., , Claes et al ., ; Fischer et al ., ; Racine et al ., ; Wolz et al ., ). Being that neuroimaging evidence has suggested that negative affect increases the rewarding value of food (Bohon & Stice, ) and that emotion dysregulation is associated with excess weight (Steward et al ., ), our results lend support to the notion that bingeing behaviours could mainly be negatively reinforcing (Berner et al ., ). Other researchers have found the tendency to act rashly when experiencing strong emotions (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Non‐compensatory PA may target certain psychopathology associated with BED and BN. For example, affective distress and dysregulation, body dissatisfaction, food cravings, and impulsivity are often associated with BED and BN. PA can improve affect immediately and reduce affective reactivity to stressors .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, FA has been associated with higher negative affect, lower self-esteem, and higher emotion dysregulation among individuals with an ED (Gearhardt et al, 2012;Pisetsky, Haynos, Lavender, Crow, & Peterson, 2017;Wolz, Granero, & Fernández-Aranda, 2017). Likewise, affective instability has been linked to dysregulated eating behaviours (i.e., bingeing and purging episodes) in women with BN (Berner et al, 2017;Wolz et al, 2016). FA has also been associated with impairments in executive functioning, namely, impulsivity: Individuals with FA in a sample of individuals with an ED diagnosis scored higher on measures of negative urgency and lack of perseverance, indicating impulsive characteristics within this ED population with FA (Granero et al, 2018;Pivarunas & Conner, 2015;Wolz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%